2015
DOI: 10.1093/ajh/hpv031
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Aldosterone Antagonists in Patients With Resistant Hypertension: A Meta-Analysis of Randomized and Nonrandomized Studies

Abstract: On the basis of the current meta-analysis, we conclude that AA is safe and effective therapy in patients with RH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(48 citation statements)
references
References 26 publications
4
39
1
4
Order By: Relevance
“…The use of this drug in RfH observed by Calhoun et al8 was higher (18%), but still lower than expected. A meta‐analysis of studies in which mineralocorticoid receptor antagonists with or without random allocation were used has shown that low‐dose spironolactone is an effective and safe additional drug to achieve BP control in many RH patients, although it is required that renal function is preserved, or only slightly or moderately reduced 18. The results of the PATHWAY‐2 (The Prevention and Treatment of Hypertension With Algorithm based therapy) study,19 the first randomized study evaluating different therapeutic options (spironolactone, doxazosin, bisoprolol, or placebo) as the fourth step in the management of patients with RH, have unequivocally demonstrated that spironolactone is the best option, at least in the short term, to improve BP control in RH subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The use of this drug in RfH observed by Calhoun et al8 was higher (18%), but still lower than expected. A meta‐analysis of studies in which mineralocorticoid receptor antagonists with or without random allocation were used has shown that low‐dose spironolactone is an effective and safe additional drug to achieve BP control in many RH patients, although it is required that renal function is preserved, or only slightly or moderately reduced 18. The results of the PATHWAY‐2 (The Prevention and Treatment of Hypertension With Algorithm based therapy) study,19 the first randomized study evaluating different therapeutic options (spironolactone, doxazosin, bisoprolol, or placebo) as the fourth step in the management of patients with RH, have unequivocally demonstrated that spironolactone is the best option, at least in the short term, to improve BP control in RH subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Spironolactone has been shown to reduce blood pressure in the general RHTN population [16,17], and in RHTN patients with heart failure with preserved ejection fraction [30]. It has been found to be a more effective BPlowering agent compared with other medication classes, as demonstrated in PATHWAY-2 [18].…”
Section: Discussionmentioning
confidence: 99%
“…Two meta-analyses of clinical and observational studies conducted from 2002 to 2013 concluded that spironolactone effectively reduces blood pressure in patients with RHTN, although the studies were often nonrandomized, and comparison between other treatment options was limited [16,17]. Subsequent to these meta-analyses, the PATHWAY-2 study, a randomized, double-blind, crossover study, evaluated patients with RHTN rotated through 12 weeks of add-on treatment with spironolactone, bisoprolol, doxazosin, or placebo [18].…”
Section: Background and Study Rationalementioning
confidence: 99%
“…Despite the fact that higher doses of eplerenone are needed, 13 the efficacy of this drug was proved with a lower incidence of side effects. 16,17 Furthermore, according to European Society of Hypertension/European Society of Cardiology guidelines for the management of arterial hypertension, eplerenone might be considered in RH. Unfortunately, the price and prescription limitations in the Czech Republic (eplerenone is indicated only in heart failure according to the summary of product characteristics) 18 do not allow wider implementation of this potent drug in resistant hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%